Membangun Kompetensi Penyuluh KUA dalam Mengukur Arah Kiblat yang Tepat: Pengabdian - Hosen Hosen; Abdul Jalil; Siti Musawwamah; Abd. Wahed; Achmad Fauzi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The majority of religious instructors at the Office of Religious Affairs (KUA) in Pamekasan Regency do not have competence in measuring qibla direction. This community service activity aims to improve the competence of religious instructors in measuring qibla direction, especially through a simple method using the shadow of the sun. Through a series of activities that included the provision of theoretical and practical materials, both indoors and outdoors, the counselors were trained to use basic tools such as tripods, arc rulers, and threads with weights. This activity also involved independent practice by each delegate of the Religious Affairs Office (KUA), the results of which were presented and evaluated by the PkM team. As a result, 85% of the participants were able to master the stages of measuring qibla direction well, and there are now trained measurers at the sub-district level. In addition, a strong partnership was established between the campus and the KUA that supports the improvement of religious services for the community. This PkM activity is expected to not only improve the competence of extension workers, but also encourage data collection and measurement of qibla direction regularly at the sub-district level.